ISOMERISM: IS THERE MISCONCEPTION? - Syahrial Syahrial; Sri Winarni (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2020)
Nine articles have been analyzed containing research results on misconceptions about isomerism. Analysis was conducted to examine the potential to causes emergence of the misconception. The analysis result are expected to be useful for teachers in learning for the same concepts. At least the teacher can avoid misconceptions that have happened before and innovate to find the right learning strategy. Isomerism can be categorized as a defined concept so that students are expected to be able to use rules for the purpose of classifying objects or events. The analysis showed 31 misconceptions experienced by grade 11 students to prospective chemistry teachers on isomerism concept. Thirty-one misconceptions are classified into three groups based on students' abilities needed to understand the concept of isomerism. The three groups are: (1) understanding the definition and application of rules; (2) spatial understanding; and (3) microscopic understanding. At this time only eleven misunderstandings were discussed, namely misunderstandings whose causes belong to the group (1). As an indicator caused misconception is inability of the sample to classify objects/events based on the attributes or characters indicated by the object/event. To teach a defined concept, it is recommended to use a strategy that contains detailed explanatory definitions and rules, examples and non-examples, and the elaboration process. In order to increase student reasoning, it is recommended to use a isomerism concept logic scheme